The impact of food-based incentive behaviors on oral health among Saudi children: a cross-sectional study - Yasir Dilshad Siddiqui; Saud Hamdan Almaeen; Ahmed Shawkat Hashem; Ahmed Ali Ahmed Almuntashiri; Mohammed Nadeem Baig; Abdullah Hammad Alshammari; Rital Jamal Alwaqid; Haifa Ali Almutairi; Raha Ahmed; Rakhi Issrani; Farooq Ahmad Chaudhary (Journal of Health, Population and Nutrition)
Abstract Background Childhood dental caries is a common and significant oral health issue globally, resulting in pain, infection, and difficulties in eating and speaking. This study aimed to investigate the impact of food-based reward behaviors on the oral health of Saudi children. Methods An observational cross-sectional study was conducted at Jouf University Hospital, Saudi Arabia. The study included 316 medically healthy children aged 4 to 10 years and their Arabic or English-speaking guardians. Data were collected through a structured questionnaire based on the Comprehensive Feeding Practices Questionnaire (CFPQ), gathering information on socio-demographic characteristics, dietary habits, oral hygiene practices, and the use of food as a reward. Clinical examinations by specialist pediatric dentists assessed the plaque index and decayed-missing-filled tooth (dmft/DMFT) scores. Statistical analyses included descriptive analysis, the Mann-Whitney test, the Kruskal-Wallis test, Spearman’s correlation, and linear regression analysis. Results Significant correlations were found between food rewards and poor oral health outcomes. Food rewards were positively associated with higher dmft/DMFT scores (r = 0.43, P < 0.001) and plaque index scores (r = 0.17, P = 0.002). Socio-demographic factors, such as parental education level and the amount of time spent with the child, were significant predictors of both food reward behaviors and oral health outcomes. Female and younger parents reported higher food reward scores, which correlated with poorer oral health in their children. Conclusion The study underscores the significant impact of food-based reward behaviors on the oral health of Saudi children. These findings highlight the need for targeted educational and intervention strategies that address cultural practices and promote healthier reward systems. By reducing sugary food rewards and encouraging non-food-based incentives, improvements in children’s oral health can be achieved.